Enforcement of Environmental Criminal Sanctions against Tourism Accommodation Companies Based on Local Wisdom and Restorative Justice - Josep Robert Khuana; I Dewa Gede Atmadja; I Gde Artha; I Nyoman Gede Sugiartha (Journal Equity of Law and Governance, 2023)
The enforcement of violations in customary law by entrepreneurs in tourism accommodation services has traditionally relied solely on administrative sanctions or fines, lacking legal regulations incorporating local wisdom and restorative justice in environmental criminal enforcement against tourism accommodation entities (empty norms). This study aims to address this gap by exploring (1) the philosophical and juridical foundations of local wisdom in environmental criminal law enforcement against tourism accommodation firms, (2) proposing a model for environmental criminal punishment against these companies, and (3) assessing the legitimacy of environmental criminal sanctions based on local wisdom and restorative justice. Employing a normative legal research method, the study reveals that (1) the philosophical and juridical underpinnings of local wisdom in environmental criminal law enforcement align with the realization of deliberative concepts stipulated in Article 18B paragraph (2) of the 1945 Constitution of Indonesia, (2) the suggested model for environmental criminal punishment adopts a corporate culture model integrated with a dual-track system, emphasizing restorative justice through penal mediation involving deliberation and consensus, (3) the validity and legitimacy of enforcing environmental criminal sanctions against tourism accommodation firms are substantiated through a proposed Bi System, intertwining the criminal justice system with penal mediation, thereby enhancing compliance and resolution within a dual-framework approach.